Investigation of the effect of the cutting fluid’s flow rate on cutting parameters in turning AISI 1045 - Mardonov , Umidjon; Yang , Ye; Shaozimova , Umida; Meliboev , Yahyojon; Ozodova , Shakhrizoda; Madaminov, Sanjarbek (Archive of Mechanical Engineering, 2026)
The use of cutting fluids (CF) is regarded as one of the most efficient supplementary methods to lower production expenses and improve the quality of machined surfaces. In this study, the influence of CF’s flow rate on machining performance of AISI 1045 was comparatively investigated in turning operations. The experimental design included different cutting velocities, feed rates, cutting depths and three flowing rates (2.5, 4, 6 l/min) of CF. 5% concentration of potassium dichromate (K2Cr2O7) in water was used as a CF. The evaluation of machining performance was studied based on thermos-electromotive force (Thermo-EMF), chip shrinkage and formation, and tool wear characterization. The results indicated that high rates of fluid flow into cutting zone yielded better results in terms of reducing the thermo-EMF, minimizing tool wear and BUE, and improving chip morphology. It was then found that increasing the fluid flow rate during cutting leads to early fracture of the chip and the segmented chip formation. In addition, with an increase in the CF flow rate from 2.5 l/min to 6 l/min, the thermo-EMF generated during turning of AISI 1045 with titanium alloyed carbide tools decreased to 13%, and flange wear to 160%.